Balance Sheet Approach for Fiscal Sustainability in Indonesia - Sriyana, Jaka; Hakim, Abdul (International Journal of Economics and Financial Issues, 2017)
This paper models fiscal sustainability in Indonesia using the measure of liabilities-to-asset ratio (LAR), a simple measure of a country’s balanced-sheet. It uses the approach of conditional Value-at-Risk (VaR), assuming normal or t distributions, to define the risky level. The conditional standard deviation in the conditional VaR is modelled using a univariate Generalized Autoregressive Heteroscedasticity (GARCH) family model. The conditional mean equation is modelled using a simple autoregressive equation. Using quarterly data from 1990 to 2014, the paper finds that the autoregressive term significantly influences the conditional mean of LAR. It also finds that both ARCH and GARCH terms significantly influence the conditional variance. Applying the conditional variance to calculate conditional VaR with 95% confidence level, and comparing the result with the actual LAR, it finds that there are no violations occurred during the period of estimation. This means that the fiscal sustainability in Indonesia is deemed safe. The violation occurs using the confidence level of 90% only. Keywords: Fiscal sustainability, liabilities-to-asset ratio, univariate GARCH, conditional Value-at-Risk JEL Classifications: H62, H63, H81